General Anaesthesia in a patient with Morvan's syndrome. Issue 2 (15th December 2013) - Tufail, Sabeen; Stacey, Mark
Summary: A 27 year old female with Morvan's syndrome presented for an elective laparoscopic ovarian cystectomy. Morvan's syndrome is a neurological disorder that results in central, autonomic and peripheral nervous system dysfunction. We outline our experience in anaesthetising a patient with this extremely rare condition and highlight the difficulties encountered when there is little written on the topic to guide anaesthetic management.